2022
DOI: 10.1166/jbt.2022.3153
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Function of miR-134 on Cognitive Function of Vascular Dementia (VD) Rats and Mechanism About Oxidative Stress and Autophagy and Cofilin 2 Level

Abstract: To discuss the mechanism of miR-134 in improving cognitive function of VD rats through regulating the oxidative stress and autophagy and reducing the expression of Cofilin 2. VD rats was established. They were disposed with miR-134 antagonist. The cerebral regulatory capacity was observed through ethology. The pathological change in CAI area of hippocampus and cerebral cortex was observed with HE staining method. The regulation of miR-134 targeting downstream was analyzed through bioinformatics. The presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Additionally, miR-134 was found to decrease Cofilin 2 levels, thereby regulating oxidative stress and autophagy in the brain. Suppression of miR-134 in VD rats improved cognitive function by modulating oxidative stress and autophagy, resulting in induced levels of Cofilin 2 [ 121 ]. Another study revealed that downregulated miR-181a can increase PTEN-induced kinase 1 ( PINK1 )/Parkin expression and enhanced mitophagy to improve mitochondrial function and enhance cognitive capabilities in VD.…”
Section: Dementia-related Diseases and Mirnasmentioning
confidence: 99%
“…Additionally, miR-134 was found to decrease Cofilin 2 levels, thereby regulating oxidative stress and autophagy in the brain. Suppression of miR-134 in VD rats improved cognitive function by modulating oxidative stress and autophagy, resulting in induced levels of Cofilin 2 [ 121 ]. Another study revealed that downregulated miR-181a can increase PTEN-induced kinase 1 ( PINK1 )/Parkin expression and enhanced mitophagy to improve mitochondrial function and enhance cognitive capabilities in VD.…”
Section: Dementia-related Diseases and Mirnasmentioning
confidence: 99%